Development and Pilot Testing of a Low Literacy Handout for Hispanic/Latino Caregivers to Promote Breastfeeding and Introduce Age Appropriate Foods for Infants - Judith C. Rodriguez; Laura Beverly; Nancy Correa-Matos; Daniel Santibanez (University of North Florida, 2008)
Based on input from four focus groups the authors developed a culturally and linguistically appropriate material (CLAM) that used a pictorial format to promote breast feeding and age-appropriate introduction of solids for Hispanics/Latinos that attended a public health clinic in the northeast region of Florida. The handout focused on five key, but simple educational messages. Clients were randomly assigned to receive 1) the physician's usual oral instruction or 2) instruction that incorporated the use, and provision of, the handout. Among the group (n=12) that received the handout the mean month for introduction of solids was 5 months compared to 4.07 months for the group (n=16) that did not receive the handout. The preliminary data suggest positive outcomes, but a more rigorous methodology and larger study sample will be needed to determine overall effectiveness of this educational material.